Action research on introducing a new methodology in business requirements elicitation - Bonggo, Janise Supan (Animo Repository, 2020)
The COVID-19 pandemic has forced all entities to adapt to the new norm, for better or for worse. To survive these difficult times, many companies have been forced to adapt. One of the ways these companies adapted was to allow most of its employees to work from home. The challenge is accomplishing the job as effectively as if the employee were in the office. This paper discusses the introduction of a new methodology in business requirements elicitation at the Land Bank of the Philippines (LBP). The bank has had its I.T. projects delayed due to problems encountered during project development. One of these problems are faulty or missing business requirements which are identified during the requirements elicitation phase. The added challenge of working from home is also exacerbating the problem. Implementing a new methodology during requirements elicitation will alleviate these problems.